Expression of PD-L1 in Hormone-naïve and Treated Prostate Cancer Patients Receiving Neoadjuvant Abiraterone Acetate plus Prednisone and Leuprolide - Calagua, Carla; Russo, Joshua; Sun, Yue; Schaefer, Rachel; Lis, Rosina; Zhang, Zhenwei; Mahoney, Kathleen; Bubley, Glenn J.; Loda, Massimo; Taplin, Mary-Ellen; Balk, Steven P.; Ye, Huihui (Clinical cancer research, 2017)
Purpose: Programmed cell death ligand-1 (PD-L1)/programmed cell death-1 (PD-1) blockade has been unsuccessful in prostate cancer, with poor immunogenicity and subsequent low PD-L1 expression in prostate cancer being proposed as an explanation. However, recent studies indicate that a subset of prostate cancer may express significant levels of PD-L1. Furthermore, the androgen antagonist enzalutamide has been shown to upregulate PD-L1 expression in prostate cancer preclinical models. In this study, we evaluated the effect of neoadjuvant androgen deprivation therapy with abiraterone acetate plus prednisone and leuprolide (Neo-AAPL) on PD-L1 expression in prostate cancer. Experimental Design: Radical prostatectomy (RP) tissues were collected from 44 patients with intermediate- to high-risk prostate cancer who underwent RP after Neo-AAPL treatment. Untreated prostate cancer tissues were collected from 130 patients, including 44 matched controls for the Neo-AAPL cases. Tumor PD-L1 expression was detected by IHC using validated anti-PD-L1 antibodies. Tumor-infiltrating CD8+ cells were analyzed in trial cases and matched controls. Expression of DNA mismatch repair genes was examined in PD-L1–positive tumors. Results: Neo-AAPL–treated tumors showed a trend toward decreased PD-L1 positivity compared with matched controls (7% vs. 21% having ≥1% positive tumor cells; P = 0.062). Treated tumors also harbored significantly fewer tumor-infiltrating CD8+ cells (P = 0.029). In 130 untreated prostate cancers, African American ethnicity, elevated serum PSA, and small prostate independently predicted tumor PD-L1 positivity. Loss of MSH2 expression was observed in 1 of 21 PD-L1–positive tumors. Conclusions: A subset of prostate cancer expresses PD-L1, which is not increased by Neo-AAPL treatment, indicating that combining Neo-AAPL treatment with PD-L1/PD-1 blockade may not be synergistic. Clin Cancer Res; 23(22); 6812–22. ©2017 AACR.